The evolution of Aotearoa New Zealand's policy discourses on Pacific climate mobilities from 2006–2021 - Dyer, Cathrine; Neef, Andreas (Frontiers in Climate, 2023)
In 2006 New Zealand government officials found themselves facing a barrage of enquiries arising from an erroneous claim contained in Al Gore’s Academy Award-winning climate change documentary An Inconvenient Truth. The documentary suggested that the government of Aotearoa had agreed to take ‘all climate refugees’ from Tuvalu, an archipelago of nine atolls and coral-reef islands in the South Pacific, as part of a planned response to climate change. At the time, New Zealand did not have any plan, or indeed any intention to create a plan, for addressing climate-induced displacement. The ensuing fifteen years saw Aotearoa’s official response evolve from one of ‘correcting misperceptions about New Zealand’s position on climate-induced migration’ to an adaptive development approach focused on Pacific-led solutions. This paper traces the evolution of that approach through a series of official reviews, focusing on the discursive frames and narratives that were employed by officials and government representatives. The current New Zealand government has expressed a desire to play a role in the development of world-leading approaches to climate-induced mobilities within the region, whilst it also seeks to avoid establishing overly broad policy precedents on climate migration that could apply beyond the Pacific. The paper discusses some of the avenues being explored by government departments, in particular the potential for existing temporary migrant programs to be developed into schemes that actively support an adaptive development framework in response to climate-related mobilities. We consider the range of possible solutions that could be contained within such a response, the opportunities for mutually beneficial approaches and the challenges that they would pose to long-accepted norms and processes embedded in the country’s current immigration programs.